Milestones of kidney transplantation in Indonesia (Medical Journal of Indonesia, 2017)
Although kidney transplantation in Indonesia has started since 1977, it has only covered less than 3% ESRD treatment methods. This indicates that the development of kidney transplantation program in Indonesia is still stagnant. Based on observation, the growth of kidney transplantation in Indonesia can be divided into several eras, which are: the birth of new treatment for ESRD era, the expected growth era, the first downfall, the stable period, the unstable period, the rebirth of kidney transplant era, and the explosive growth era. Many factors contribute to this issue including the government policy, the funding problems, the limited donor pool, the dissenting cultural views, the number of human resources, the need for multi-disciplinary approach, and the life-after-graft care. However, many improvements have been made to increase kidney transplantation i.e. the government support for opening new kidney transplant centers, the use of minimally invasive techniques, the development of pediatric kidney transplant, and National Insurance coverage for transplantation. These conditions are expected to improve the number of kidney transplantation in Indonesia.